ERROR ANALYSIS ON GENERAL ENGLISH WRITING TASK IN 17-14A CLASS AT LONDON SCHOOL OF PUBLIC RELATION JAKARTA - ASTUTI, DIAN NOVIANA (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Error Analysis, error, types of error English is an international language, being either a first, second or foreignlanguage for various countries around the world. In the process of learning language, Indonesian students surely make errors. It is understandable since the rule of Bahasa Indonesia and English is different. This research aims: (1) to identify the types of errors, and (2) to find the most frequently error in General English writing task in 1714A class at London School of Public Relation Jakarta.This research is designed by using descriptive qualitative research and document analysis to answer the problems of the study. The data were collected from thirty General English writing task produced by students in 17-14A class at London School of Public Relation. The researcher analyzed the data using the theory from Dulay, Burt, and Krashen (1982) about Surface Strategy Taxonomy.The results of this research showed that the students did some types of errorswhen they wrote an unforgettable moment in their life. Those errors are omission, addition, misformation, and misordering. Omission was divided into some parts namely, omission of article, omission of “be”, omission of preposition, omission of plural marker (-s/-es), omission of possessive adjective, omission of subject, and omission of verb. Then, addition was divided into some types namely, addition of adjective, addition of article, addition of “be”, addition of noun, addition of preposition, addition of plural marker (-s/-es) and addition of verb. Misformation was also divided into some types namely, misformation of adverb, misformation of „be‟, misformation of infinitive “to”, misformation of preposition, and misformation of verb. The last is misordering.The researcher suggests to the next writers who want to conduct the similarresearch use the different object and analyze the errors with other theories. Another suggestion is to use the same theory but with the different object like textbook or article for the data.